Algumas curvas notáveis: aplicações e construções com o uso do software Winplot - Santos, Francisco Filipe Passos dos (2016)
The lack of significance of mathematics in the reality of the students gradually distances them from this science. Without contextualization and lack of connection between other sciences, mathematics may become, in a young man mind, a meaningless science. The curves exemplify the quite importance that this science enjoyed in the development of different cultures and denotes how formulas and equations assumed an important role in several problems. Furthermore, the daily applications of the curves are presented in order to prove how math is used in buildings, music and arts, thereby giving a meaning to this science. Nowadays, the great ease of how technology has been provided, it became important the use of tools called TIC’s. The present work uses the Winplot tool for the construction of curves. Moreover, it allows the student besides the preview of graphics, various functions, which may get information to expand his/her knowledge.